The Business Plot in the American press - Galka, Bradley M. (Kansas State University, 2017)
In the fall of 1934 Major General Smedley Butler, U.S.M.C. (ret.) testified before Congress that he had been approached by a representative of a cabal of wealthy Wall Street bankers, powerful industrial magnates, and shady political operatives to lead a fascist coup to overthrow the administration of President Franklin D. Roosevelt. Congress investigated Butler’s allegations of a conspiracy against the government and deemed them to be true. The American news media, however, was noticeably divided in the nature of their coverage of the congressional investigation. Previous historians have claimed that elements of the American news media were markedly sympathetic toward fascism in the United States during the 1930s. An analysis of the newspaper coverage of this investigation reveals a stark contrast between ways in which media outlets headed by individuals suspected of fascist sympathies portrayed the story as opposed to media outlets known to be editorially anti-fascist. These findings lend credence to previous historians’ claims about identifiably pro-fascist strains in the American media during the time in question.
Keywords: Fascism; American Media; Business Plot; Congress